Pengaruh Pembelajaran Melalui Pelacakan Mata terhadap Keterampilan Penahanan Kaki dan Pertahanan Lemparan pada Pegulat Greco-Roman Pemula - Monaf Ibrahim Hassan (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study examined the effects of Eye-Tracking–based Learning on ground pinning skill and defense against throws in novice Greco-Roman wrestlers, assessing whether integrating perceptual-cognitive exercises into conventional Learning enhances technical and anticipatory performance. Materials and methods. 32 male wrestlers aged 12–14 years were randomly assigned to an experimental group (n = 16) or a control group (n = 16). Both groups completed an eight-week program with three 90-minute sessions per week, while the experimental group additionally performed Eye-Tracking exercises aimed at improving ground pinning skill and defense against throws. Results. The experimental group showed substantial improvements in ground pinning skill (Pre: 12.4 ± 1.8; Post: 17.6 ± 1.5) and defense against throws (Pre: 11.9 ± 2.0; Post: 16.4 ± 1.7), whereas the control group showed only modest gains. Post-intervention comparisons revealed significantly higher performance in the experimental group for both skills. Repeated-measures ANOVA confirmed significant main effects of group, time, and their interaction, demonstrating the effectiveness of the Eye-Tracking intervention. Conclusions. Eye-Tracking–based Learning effectively enhances technical execution and anticipatory defensive abilities in novice Greco-Roman wrestlers. Incorporating perceptual-cognitive exercises into conventional wrestling programs can optimize skill acquisition, improve tactical responsiveness, and accelerate performance development, supporting coaches in preparing athletes for competitive success.